Isolation and Characterization of Precise Dye/Dendrimer Ratios. Issue 16 (6th March 2014) - Dougherty, Casey A.; Furgal, Joseph C.; van Dongen, Mallory A.; Goodson, Theodore; Banaszak Holl, Mark M.; Manono, Janet; DiMaggio, Stassi
Abstract Fluorescent dyes are commonly conjugated to nanomaterials for imaging applications using stochastic synthesis conditions that result in a Poisson distribution of dye/particle ratios and therefore a broad range of photophysical and biodistribution properties. We report the isolation and characterization of generation 5 poly(amidoamine) (G5 PAMAM) dendrimer samples containing 1, 2, 3, and 4 fluorescein (FC) or 6‐carboxytetramethylrhodamine succinimidyl ester (TAMRA) dyes per polymer particle. For the fluorescein case, this was achieved by stochastically functionalizing dendrimer with a cyclooctyne "click" ligand, separation into sample containing precisely defined "click" ligand/particle ratios using reverse‐phase high performance liquid chromatography (RP‐HPLC), followed by reaction with excess azide‐functionalized fluorescein dye. For the TAMRA samples, stochastically functionalized dendrimer was directly separated into precise dye/particle ratios using RP‐HPLC. These materials were characterized using 1H and 19F NMR spectroscopy, RP‐HPLC, UV/Vis and fluorescence spectroscopy, lifetime measurements, and MALDI.